Reliability and validity of the dutch eating behavior questionnaire in an online format for university students from low-income regions in a pandemic context: A 24 hour MESYN study - de Carvalho, Millena Vaz; Cardoso, Antonio Gibran de Almeida; Feuerstein, Shirley Cunha; Sousa, Rosana Rodrigues de; Collese, Tatiana Sadalla; Torres-Leal, Francisco Leonardo; Nascimento-Ferreira, Marcus Vinicius; De Moraes, Augusto Cesar Ferreira (Frontiers in Epidemiology, 2023)
Objective To test the reliability and validity of the Dutch Eating Behavior Questionnaire (DEBQ) in an online format in university students from low-income regions. Methods We applied the questionnaire to a sample of 195 and 117 university students from a low-income region (Gini index of 0.56) to study validity and reliability, respectively. The DEBQ consists of 33 items on eating behavior in three dimensions/factors: emotional eating, restrained eating and external eating. The questionnaire was administered twice at 2-week intervals. We tested the reliability via temporal stability and internal consistency and construct validity via exploratory and confirmatory factor analysis. Results For reliability, we identified an acceptable Spearman correlation coefficient (rho > 0.30 and p < 0.05) and Cronbach's alpha (α ≥ 0.70) for all DEBQ items. In the exploratory analysis, we identified 6 factors representing a mix of original and additional factors, with an explained variance of 69.1%. In the confirmatory analysis with structural equation modeling, we observed better global model adjustment for the 6-factor model with the Tucker–Lewis index and comparative fit index closer to one, as well as root mean square error of approximation closer to zero than the original (3-factor) model. Using generalized structural equation modeling, we also observed a better fit in latent class modeling for the 6-factor model (AIC: 16990.67; BIC. 17874.38) than for the 3-factor model (AIC: 17904.09; BIC: 18342.67). Conclusion The online format of the DEBQ has acceptable reliability and validity for measuring eating behavior in university students from low-income regions.